Community-onset Staphylococcus aureus Surveillance Programme annual report, 2012. - Coombs, Geoffrey; Daly, D.; Pearson, J.; Nimmo, G.; Collignon, P.; McLaws, M.; Robinson, J.; Turnidge, J.; Australian Group on Antimicrobial Resistance (2014)
In 2012, the Australian Group on Antimicrobial Resistance (AGAR) conducted a community-onset period-prevalence survey of clinical Staphylococcus aureus isolated from hospital outpatients and general practice patients including nursing homes, long term care facilities and hospice patients. Day surgery and dialysis patients were excluded. Twenty-nine medical microbiology laboratories from all state and mainland territories participated. Isolates were tested by Vitek2® (AST-P612 card). Results were compared with previous AGAR community surveys. Nationally, the proportion of S. aureus that were methicillin-resistant S. aureus (MRSA) increased significantly from 11.5% in 2000 to 17.9% in 2012 (P<0.0001). Resistance to the non-ß-lactam antimicrobials varied between regions. No resistance was detected to vancomycin, teicoplanin or linezolid. Resistance in methicillin susceptible S. aureus was rare apart from erythromycin (12.8%) and was absent for vancomycin, teicoplanin, linezolid and daptomycin. The proportion of S. aureus characterised as health care-associated MRSA (HA-MRSA) was 5.1%. Three HA-MRSA clones were characterised, with 72.9% and 26.4% of HA-MRSA classified as ST22-IV [2B] (EMRSA-15) and ST239-III [3A] (Aus-2/3 EMRSA) respectively. Multi-clonal community-associated MRSA (CA-MRSA) accounted for 12.5% of all S. aureus. Regional variation in resistance in MRSA was primarily due to the differential distribution of the 2 major HA-MRSA clones; ST239-III [3A] (Aus-2/3 EMRSA), which is resistant to multiple non-ß-lactam antimicrobials, and ST22-IV [2B] (EMRSA-15), which is resistant to ciprofloxacin and typically erythromycin. Although the majority of CA-MRSA were non-multi-resistant, a significant expansion of Panton-Valentine leukocidin (PVL) positive CA-MRSA clones has occurred nationally. The mean age of patients (31.7 years, 95% CI 28.9-34.5) with a PVL positive CA-MRSA infection was significantly lower (P<0.0001), than the mean age of patients with a PVL negative CA-MRSA infection (55.7 years, 95% CI 50.7-60.6). This shift in the molecular epidemiology of MRSA clones in the Australian community will potentially increase the number of young Australians with skin and soft tissue infections requiring hospitalisation.